2010
DOI: 10.1590/s0102-05362010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de alface em cultivo hidropônico sob dois níveis de condutividade elétrica

Abstract: O objetivo do trabalho foi comparar cultivares de alface de folhas soltas lisas, submetidas a estresse osmótico em soluções nutritivas sob cultivo hidropônico. Foram realizados dois experimentos, cada um com uma condutividade elétrica (C.E.) de 2,0 dS m-1 e 2,5 dS m-1. Os tratamentos foram as cultivares de alface Babá de Verão, Floresta, Luisa, Manoa, Regina 579, Saia Véia e Vitória Verdinha. O delineamento experimental foi blocos casualizados, com três repetições. A colheita foi feita aos 45 dias após a semea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
1
3
3
8
Order By: Relevance
“…These results corroborate those found by other researchers, who observed varied responses of different lettuce cultivars subjected to salinity (Magalhães et al, 2010;Paulus et al, 2010;Oliveira et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…These results corroborate those found by other researchers, who observed varied responses of different lettuce cultivars subjected to salinity (Magalhães et al, 2010;Paulus et al, 2010;Oliveira et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…The number of leaves obtained in the present study is lower than the mean of 32 leaves reported by Magalhães et al (2010), and this difference can be explained by the higher electrical conductivity (EC) of the nutrient solution used by these authors (2.5 dS m -1 ). Comparing mineral and modified solutions, i.e., BM with BO, FM with FO and so on, the mineral solutions led to higher means of number of leaves, which can be associated with the lower availability of nutrients to the plants with the use of the modified solutions, due to the capacity of adsorption of ions by organic compounds from the biofertilizers used in the production of these solutions, because, regardless of the plot, the EC was maintained close to 1.5 dS m -1 .…”
Section: Resultscontrasting
confidence: 85%
“…Various studies have already been conducted with the cultivation of this vegetable using the technique of hydroponics, such as Magalhães et al (2010), Paulus et al (2012) and Sarmento et al (2014). However, all refer to the use of mineral nutrient solutions, particularly the solution of Furlani (1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the first harvest, we noticed 61.9% more leaves in plants produced from the greater (50 cm³ cell -1 ) to the lower volume (10 cm³ cell -1 ) and 62.8% in the second harvest, showing similar plant growth in the two harvests ( Figure 1B). Growing several lettuce cultivars under NFT system using seedlings produced in phenolic foam trays (8 cm³ cell -1 ) were found 27 leaves plant -1 for all the studied varieties at 30 DAT (Magalhães et al, 2010). Using the same cell volume and harvest season at 39 DAT for Grand Rapids type lettuce, the authors observed 26.4 leaves plant -1 (Casaroli et al, 2003).…”
Section: Resultsmentioning
confidence: 95%